The politics of environmental policy in Russia - Feldman, David Lewis; Blokov, Ivan.; Edward Elgar Publishing (Cheltenham : Edward Elgar Pub. Ltd., 2012)
The authors, renowned experts in the field, explore efforts to develop a mature civil society in Russia, and analyse the policy views of environmental groups, the media, and the scientific community. Three important case studies underpin the study: suspended plans to build an oil pipeline near Lake Baikal; management of Cold War-generated radioactive waste at Chelyabinsk; and public reaction to the introduction of genetically modified foods. The conclusion is that although civil society groups face obstacles in the form of apathy, state-imposed constraints on their activities, and agency reluctance to confer on decisions, there are some successes in reversing decisions due in part to NGO pressures yielding reform.
1. Civil society, environment and Russian politics post-1991 -- 2. Russia's environmental challenges and their management -- 3. Environmental civil society through Russian eyes : stakeholder views -- 4. Case studies and their insights into civil society growth : Lake Baikal, Chelyabinsk and genetically modified food -- 5. Interpreting civil society : challenges, change and environmental significance -- 6. Conclusions : the bad, the good and the uncertain.
Includes bibliographical references and index.
Keywords: Environmental policy -- Russia (Federation); Political sociology; Electronic books